2008
DOI: 10.1093/jnci/djn365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disrupting Seven-in-Absentia Homolog 2 Function on Lung Cancer Cell Growth

Abstract: SIAH-2 may be a viable target for novel anti-RAS and anticancer agents aimed at inhibiting EGFR and/or RAS-mediated tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 58 publications
4
97
0
Order By: Relevance
“…Upon these findings, we speculate that downstream factors of Siah1 other than HIF1α may affect tumour progression. Siah was initially identified as a tumour suppressor gene [12], although recent studies have shown that knock-down of Siah by shRNA could significantly impede lung and pancreatic tumour growth in vitro and in vivo, indicating that expression of Siah itself promotes tumour growth [9,13,23]. Another study in breast cancer also showed that increased Siah expression was related to the aggressiveness of breast cancers [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon these findings, we speculate that downstream factors of Siah1 other than HIF1α may affect tumour progression. Siah was initially identified as a tumour suppressor gene [12], although recent studies have shown that knock-down of Siah by shRNA could significantly impede lung and pancreatic tumour growth in vitro and in vivo, indicating that expression of Siah itself promotes tumour growth [9,13,23]. Another study in breast cancer also showed that increased Siah expression was related to the aggressiveness of breast cancers [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, understanding the molecular mechanisms that regulate Siah expression will likely provide new insights into the pivotal function of Siah in cancer biology and should contribute to novel anti-cancer strategies [12,13,25]. The relationship between Siah1 and HIF1α expression and patient prognosis was examined by Kaplan-Meier analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in other cancers, such as liver and gastric cancers, low levels of Siah1 expression promoted cancer progression [31] . A dominant negative Siah protein was also found to inhibit ERK signaling and cell proliferation, increase apoptosis induction, and reduce tumorigenesis of A549 human lung cancer cells, when injected into nude mice [32] . In addition, inhibition of the expression of Siah had an anti-tumorigenic effect in mouse melanoma, SW1 cells, and breast cancer cells [33] .…”
Section: Function Of Siah As a Tumor Sup-pressor Protein And Its Rolementioning
confidence: 98%
“…The role of Siah2 in tumor development has been extensively studied. Inhibition of Siah reportedly attenuates breast, pancreatic, lung, prostate, and melanoma tumors (13)(14)(15)(16). Mechanistically, Siah2 contributes to tumor development and metastasis via its control of diverse substrates, as shown in a melanoma model (14).…”
mentioning
confidence: 99%